Eye tech - Abdul Aziz, Ahlam; Mohd Azhar, Muhammad Amir Farhan; Muhammad Azly, Muhammad Aiman; Abdul Jabar, Muhammad Irfan; Mohd Kamal, Khairun Liyana (Universiti Teknologi MARA, Kedah, 2023)
Eye-T are sophisticated and high-tech glasses. Eye-T glasses frames are made of metal and plastic. The lens is made of various types of plastic metal and has a durable mirror. The beautiful and stylish shape of the glasses is suitable for both men and women. These glasses can help our community and target audience to facilitate every task and work they do. Cooperation with a big company like Google helps Eye-T to get more information and solve various problems. The use of a small and light chip to analyze information makes Eye-T does not look like high-tech glasses but look like normal and stylish glasses Spectacles are the important thing if there are myopic or want to cover their eyes from the sun to care about the eyes. We have innovated Spectacles as our main thing to help society play with the technology so they can get exposure to the new technology.